A triangular Wilkinson power divider with spaced output ports - Khalaj-Amirhosseini, M.; Moghavvemi, M.; Attaran, A. (2011)
This paper proposes an idea to modify the conventional Wilkinson power dividers to have physically spaced output ports. The well-known internal resistor of Wilkinson power divider is now connected to output ports by two additional transmission lines to create a triangular shape power divider. Several modified power dividers are designed at frequency of 1.0 GHz and one of them is fabricated and measured. The measured results of the fabricated diplexer have very good agreement with the theoretical results.